Correlation between Intraoperative Imprint Cytology and Histopathological Diagnosis of Sentinel Lymph Nodes in Clinically Node Negative Breast Carcinomas (GAIMS Journal of Medical Sciences, 2023)
Introduction: Sentinel lymph node imprint cytology is a reliable method of assessment of axillary lymph node status in clinically node-negative breast cancers.This technique is advantageous in resource-poor settings where cryostats are not available. The results are obtained in a short time, and hence they can be used intra operatively to arrive at a conclusive evidence of metastatic disease in axillary lymph nodes, thereby guiding further treatment. The objective of this study was to compare imprint cytology and histopathological diagnosis of sentinel lymph node in clinically node-negative breast cancers.Methods: This was a cross-sectional study conducted among 53 female patients with clinically node- negative breast cancer who had undergone mastectomy with sentinel lymph node sampling. Imprint smears of the sentinel node were prepared and interpreted either as positive or negative based on the presence of metastasis. The results were compared with histopathological diagnosis, and the sensitivity and specificity of the procedure were determined.Results: Out of the 53 cases, 6 cases were diagnosed with metastatic carcinomatous deposit in the axillary nodes, both by imprint cytology and histopathology. Only one case which was reported as negative for metastatic deposit in the lymph node by imprint cytology was diagnosed later by histopathology to have metastatic carcinomatous deposit. 46 cases were negative for metastatic carcinoma, both by imprint cytology and histopathology of axillary lymph node. Based on the above results, the sensitivity of Sentinel lymph node imprint cytology was 85.71% and specificity was 100%.Conclusion: Intraoperative imprint cytology of axillary lymph nodes was found to have high sensitivity and specificity in diagnosing metastatic disease in resource-poor settings.